The role-plays for the development of oral expression skills in students of the first degree primary - Laines Ochoa, Cynthia Nataly (2015)
This paper describes the process and results of the research about oral expression level through a roleplay activities program for the first grade primary students from school No. 10003 Campodónico – Chiclayo. The program involves the implementation of 20 learning sessions for increasing the level of oral comprehension and oral expression capacities. The influence of the role-play activities was determined. A diagnostic study was made and the instrument was a rating scale in its version of pre-test. It showed a deficit on the role-plays being the lower and middle level as the most representative. The application of the twenty learning sessions and the use of the rating scale version of Post Test showed that the students were placed in the high and middle level; verifying the accuracy and relevance of roleplay strategy in the process of school learning.